The optical calibration system for the CTA-North Large Sized Telescope camera - Iori M.; Ferrarotto F.; Girardi A.; Lunadei R.; Recchia L. (EPJ Web of Conferences)
The first Large-Sized Telescope (LST-1) for the Northern Site of the Cherenkov Telescope Array Observatory (CTAO) was inaugurated in October 2018 at the Observatorio del Roque de Los Muchachos (ORM) on La Palma (Canary Island). Other three LSTs are planned to be operational from 2026 in the same site. The LST camera requires a precise and regular calibration. The CaliBox is designed to fulfill the requirements for the camera calibration: monitoring the photon flux to guarantee the laser stability, uniform illumination, and intensity range. We present the design and performance of the optical system, photon flux monitor, related electronics, and evaluations and tests of the photon flux at the camera plane carried out at the INFN Rome1 Electronic laboratory.